PENGEMBANGAN BAHAN AJAR BIOLOGI DASAR BERBASIS MOBILE LEARNING MENGGUNAKAN ADOBE FLASH Cs6 - Fenny Hasanuddin; Rukmelia Rukmelia (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2020)
The aim of this research is to develop a valid teaching material of basic biology subjects based on mobile learning using Adobe Flash Cs6 at the Muhammadiyah University of SidenrengRappang. The type of study is research and development (R&D), and the research implementation procedures were based on the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. Nevertheless, this research is limited only until the third step (Development). The Instruments in this study were the validation sheet; validation sheets for material experts, and media experts. The data analysis technique applied was validation data analysis. Data collected by using the instrument then developed and analyzed quantitatively. The result showed a valid category from both material experts with a value rate of 5, and media expert validator with a value rate of 5 4.95. It means that teaching material based on mobile learning (Adobe Flash Cs6) available in basic biology subjects at the Muhammadiyah University of SidenrengRappang.